Technical efficiency and the scale of sisal production in the state of Bahia (Brazil) - Soares Alves, Adrielle Victoria (2017)
The purpose of this study is to measure the technical efficiency index of the sisal local productive arrangement in Bahia. Data envelopment analysis (DEA) is used to analyze data obtained in 2015 through research conducted directly with micro, small, and medium-sized enterprises. The results show that sisal companies can reduce input costs on average by 39% with the constant return model and by 21% with the variable return model, without compromising production. It was also observed that increasing returns of scale prevail.